(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The purpose of this research work was to develop and optimize the Solid Lipid Nanoparticles (SLNs) of Tazarotene for the effective topical delivery in the treatment of psoriasis. Tazarotene loaded SLNs were prepared by hot homogenization followed by the ultrasonication using Taguchi’s design and based on the results further investigation was made using central composite design. The lipid Dynasan-116, surfactant poloxomer-188 and co surfactant egg lecithin resulted in better percent drug loading and evaluated for particle size, zeta potential, TEM, drug entrapment efficiency, in vitro drug release and stability. All parameters were found to be in an acceptable range. In vitro drug release of optimized SLN formulation (F1) was found to be 98.12 ± 1.52%, whereas pure drug release was 42.12 after 60 min. The optimized formulation was incorporated into the gel. The release rate (flux) of tazarotene across the membrane and excised skin differs significantly. The accumulative amount of Tazarotene in skin from SLN based gel formulation and marketed gel were 41.12 ± 0.12 mg and 30.02 ± 0.04 mg respectively. This result supported our hypothesis made in skin permeation studies on rat skin. From histopathological studies the microscopic observations indicate that the optimized SLN formulation, SLN based gel formulation and marketed gel has no significant effect on the microscopic structure of the skin. The skin-irritation studies indicated that SLN based gel containing Tazarotene did not show any sign of skin irritation as compared to moderate erythema shown by marketed gel formulation (Tazret® gel) after 72 h of application. Thus, SLN based gel formulation demonstrated advantage over marketed formulation in improving the skin tolerability of Tazarotene indicating their potential in improving patient acceptance and topical delivery of Tazarotene.